Durability of steel fiber reinforced self-compacting concrete - Frazão, Cristina Maria Vieira (2015)
Durability is one of the most important aspects of concrete due to its fundamental incidence on the serviceability working conditions of concrete structures. Research on the durability of steel fiber reinforced self-compacting concrete (SFRSCC) is still scarce, particularly in the aspects of corrosion resistance, which did not yet demonstrate clearly whether the corrosion of steel fibers may or may not lead to cracking and subsequent spalling of the surrounding concrete. For conventional concrete, without steel fibers, there are some widespread used durability indicators, which applicability to SFRSCC and its common values are practically unknown. For this purpose, an experimental work with SFRSCC and self-compacting concrete (SCC) specimens was carried out in order to characterize their mechanical properties and evaluate durability indicators. The results showed that the addition of steel fibers to SCC was very effective in terms of increasing the post-cracking flexural resistance and the energy absorption, and did not affect significantly the selfcompacting requisites and the durability indicators of SCC.